IDDF2020-ABS-0064 Three-Day Postoperative Antimicrobial Prophylaxis Can Reduce the Incidence of Postoperative Infection in Primary Hepatocellular Carcinoma: A Multicenter Retrospective Study. (18th November 2020) - Chen, Zebin; Wang, Yuanqi; Liang, Ruiming; Lai, Jiaming; Li, Dongming; Li, Shaoqiang; Lei, Kai; Zhou, Qian; Peng, Baogang
Abstract : Background: Postoperative infection in primary hepatocellular carcinoma (HCC) may cause bad consequences, even affect overall survival. But the evidence of using postoperative antimicrobial prophylaxis (AMP) in HCC was not sufficient enough. We aimed to explore the relationship between postoperative AMP and infection after hepatectomy. Methods: We retrospectively collected 1648 HCC patients who underwent hepatectomy from three tertiary hospitals. The incidences of postoperative infection, including surgical site infection (SSI) and remote site infection (RI) were recorded and calculated. Univariable and multivariable Cox regression analyses were performed to explore risk factors of postoperative infection. Inverse probability of treatment weighting (IPTW) analysis was also performed to reduce the selection bias. Results: The overall infection rate was 9.7% (160/1648), including 8.1% of SSI and 2.3% of RI. Multivariable analysis revealed that the duration of postoperative AMP was negatively related to the incidence of postoperative infection significantly (OR 1.39, 95 per cent c.i. 1.28 to 1.52; P < 0.01). And 3-day regimen seemed to be the shortest duration of postoperative AMP to gain the lowest incidence of postoperative infection. In the subgroup analysis between patients received 0-day and 3-day postoperative AMP, using postoperative AMP for 3 days was an independent protective factor of infection (OR 0.04, 95 per cent c.i. 0.01 to 0.29; P <0.01). IPTW analysis showed consistent results with those of previous analysis ( P =0.01). Conclusions: Postoperative AMP is necessary for HCC patients to prevent postoperative infection. Using antibiotics based on the experience of surgeons for 3 days after surgery might be proper. (Figure 1 )